Extended diffusion theory: Recovering dynamics from biased/accelerated molecular simulations. Issue 9 (22nd December 2020) - Rapallo, Arnaldo; Gaspari, Roberto; Grasso, Gianvito; Danani, Andrea
Abstract: Dynamical properties are of great importance in determining the behavior of synthetic and natural molecules, but capturing them by computational methods is a nontrivial task. Very often the time scales of the relevant phenomena are far beyond the typical time windows accessible by classical Molecular Dynamics (MD) simulations, currently limited to the order of microseconds on standard laboratory workstations. On the other hand, biased and accelerated simulations allow for fast and thorough exploration of the molecular conformational space, but they lose the dynamic information. The problem of recovering dynamics from biased/accelerated simulations is a very active field of research, but no totally robust/reliable solutions have been given yet. In this paper it is shown how the Smoluchowski equation, in the framework of Diffusion Theory (DT), can be used to bridge this gap, and dynamical properties, in the form of time correlation functions (TCFs), can be extracted also from such kind of simulations. DT is first extended (EDT) to express the mobility tensors entering the Smoluchowski operator in terms of a recently introduced unified and regularized Rotne–Prager–Yamakawa approximation, [P. J. Zuk, E. Wajnryb, K. A. Mizerski, P. Szymczak, J. Fluid. Mech . 2014, 741, R5, 1–13] also involving mixed rotation‐translation contributions, and rotation‐rotation terms beside the classical translation‐translation ones, so far used in DT. Then, the method is applied to recover the dynamics of a nontrivial example of a peptide in explicit water from the first 200 ns of a Replica Exchange Molecular Dynamics simulation, which is a popular computational method that destroys the long time dynamics. EDT dynamics were found to favorably compare against those coming from a standard MD simulation of the same system, requiring a time window of 30 μs to converge. This result shows that EDT is a tool of practical value to recover the long time dynamics of systems in diffusive regimes from biased/accelerated simulations, to be exploited in those cases when direct evaluation by standard MD is unfeasible. Abstract :